2021
DOI: 10.3389/fevo.2021.704070
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Genes in Lemur Gut and Soil Microbiota Along a Gradient of Anthropogenic Disturbance

Abstract: The overuse of man-made antibiotics has facilitated the global propagation of antibiotic resistance genes in animals, across natural and anthropogenically disturbed environments. Although antibiotic treatment is the most well-studied route by which resistance genes can develop and spread within host-associated microbiota, resistomes also can be acquired or enriched via more indirect routes, such as via transmission between hosts or via contact with antibiotic-contaminated matter within the environment. Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…Other factors that may contribute to this difference in AMR include movement and access to shared water points, but these could not be investigated in this study. Another study found a larger number of β-lactam–resistant Enterobacteriaceae in plains zebra in Tanzania and provided a behavioral explanation: plains zebras are frequently found near human dwellings and may come into contact with human waste and be exposed to contamination by resistant bacteria (Katakweba et al 2015; Bornbusch and Drea 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that may contribute to this difference in AMR include movement and access to shared water points, but these could not be investigated in this study. Another study found a larger number of β-lactam–resistant Enterobacteriaceae in plains zebra in Tanzania and provided a behavioral explanation: plains zebras are frequently found near human dwellings and may come into contact with human waste and be exposed to contamination by resistant bacteria (Katakweba et al 2015; Bornbusch and Drea 2021).…”
Section: Discussionmentioning
confidence: 99%
“…More information is needed to understand the microbial composition of healthy gut microbiota in wild and captive nonhuman primates. For example, studies of antimicrobial resistance and social environment are crucial to connect microbiotal information to animal health (Barelli et al, 2021; Bornbusch & Drea, 2021; García et al, 2020; Kuthyar et al, 2019; Perofsky et al, 2017; Sarkar et al, 2020; Tsukayama et al, 2018; Tung et al, 2015; Zhu et al, 2021; Zvoboda, 2017). A decrease in the diversity of intestinal microbiome species may be associated with diseases and inflammation thus aiding pathogenic microorganisms (Battaglioli et al, 2018; Cho & Blaser, 2012; Hale et al, 2019; Petersen & Round, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the gut microbiota of nonhuman primates (NHPs) is observably affected by captive rearing (Campbell et al, 2020; Littleford‐Colquhoun et al, 2019), with lower bacterial alpha‐diversity and humanlike microbes (Clayton et al, 2016; Kohl et al, 2014; Metcalf et al, 2017; Uenishi et al, 2007). These changes in gut microbiota profiles may be linked to reduced reproduction and a greater risk of disease infection in captive animals (Amato, Metcalf, et al, 2016; Baros Jorquera et al, 2021; Bornbusch & Drea, 2021; Schluter et al, 2020). Previous research on captive baboons (Papio kindae) found that the relative abundance of drug‐resistant bacteria significantly increased in their gut compared to wild baboons (Tsukayama et al, 2018).…”
Section: Introductionmentioning
confidence: 99%